Self‐Reported Sleep Disturbances over the Menopausal Transition and Fracture Risk: The Study of Women's Health Across the Nation - Jane A. Cauley; Howard M. Kravitz; Kristine Ruppert; Yinjuan Lian; Martica J. Hall; Sioban D. Harlow; Joel S. Finkelstein; Gail Greendale (JBMR Plus, 2023)
Abstract Sleep disturbances are common and may impact fracture risk directly by influencing bone turnover or indirectly through shared risk factors or mediators. To investigate the association between self‐reported sleep disturbances across the menopausal transition (MT) and fractures, we prospectively studied 3101 women enrolled in the Study of Women's Health Across the Nation (SWAN). At each of 14 study visits spaced approximately 18 months apart, a standardized validated scale ascertained trouble falling asleep, waking up several times during the night, and waking up earlier than planned. Two time‐varying exposures were modeled: presence of any of the three disturbances at least three times per week and waking up several times during the night at least three times per week. Base models adjusted for fixed (race/ethnicity, study site) and time‐varying characteristics (age, body mass index, and MT stage). Fully adjusted models also included time‐varying bone beneficial and detrimental medications, smoking, alcohol, physical activity, diabetes, depression and sleep medications, and depressive symptoms. Women who experienced a fracture were more likely to report a greater frequency of having trouble falling asleep, waking up several times, and/or waking up earlier: 35% versus 30% at baseline, p = 0.02. In the base models, women who had any of the three sleep disturbances at least three times per week had a higher risk of any fracture, odds ratio (OR) = 1.23 (95% confidence intervals, 1.02, 1.48) and nontraumatic fracture, OR = 1.36 (1.03, 1.80). These associations were largely attenuated to nonsignificance in the fully adjusted model. Sensitivity analyses limiting our sample to 2315 SWAN women enrolled in the bone mineral density (BMD) centers yielded similar results. Additional adjustment for femoral neck BMD had no effect on our results. In conclusion, self‐reported sleep disturbances were associated with an increased risk of fractures, but these associations likely reflect shared risk factors or factors in the causal pathway. © 2023 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.